Activation of cannabinoid 2 receptors protects against cerebral ischemia by inhibiting neutrophil recruitment - Murikinati, Sasidhar Reddy; Jüttler, Eric; Keinert, Timo; Ridder, Dirk; Muḥammad, Sajjad; Waibler, Zoe; Ledent, Catherine; Zimmer, Andreas; Kalinke, Ulrich; Schwaninger, Markus (The FASEB journal, 2010)
Activation of the cannabinoid 2 receptor (CB2) reduces ischemic injury in several organs. However, the mechanisms underlying this protective action are unclear. In a mouse model of ischemic stroke, we show that the CB2 agonist JWH-133 (1 mg • kg”1 • d”1) decreases the infarct size measured 3 d after onset of ischemia. The neuroprotective effect of JWH-133 was lost in CB2-deficient mice, confirming the specificity of JWH-133. Analysis of bone marrow chimeric mice revealed that bone marrow-derived cells mediate the CB2 effect on ischemic brain injury. CB2 activation reduced the number of neutrophils in the ischemic brain as shown by FACS analysis and by measuring the levels of the neutrophil marker enzyme myeloperoxidase. Indeed, we found in vitro that CB2 activation inhibits adherence of neutrophils to brain endothelial cells. JWH-133 (1 µM) also interfered with the migration of neutrophils induced by the endogenous chemokine CXCL2 (30 ng/ml) through activation of the MAP kinase p38. This effect on neutrophils is likely responsible for the neuroprotection mediated by JWH-133 because JWH-133 was no longer protective when neutrophils were depleted. In conclusion, our data demonstrate that by activating p38 in neutrophils, CB2 agonists inhibit neutrophil recruitment to the brain and protect against ischemic brain injury.— Murikinati, S., Jüttler, E., Keinert, T., Ridder, D. A., Muhammad, S., Waibler, Z., Ledent, C., Zimmer, A., Kalinke, U., Schwaninger, M. Activation of cannabinoid 2 receptors protects against cerebral ischemia by inhibiting neutrophil recruitment. FASEB J. 24, 788-798 (2010). www.fasebj.org